Mathematical modeling of the protein corona: implications for nanoparticulate delivery systems. (May 2014) - Dell'Orco, Daniele; Lundqvist, Martin; Linse, Sara; Cedervall, Tommy
This article discusses the role of the protein corona in delivery systems with tagged nanoparticles and how knowledge of the protein corona can help in optimizing delivery. The basic question is whether and how the binding of proteins and other biomolecules at the nanoparticle surface interfere with the interaction between a tag and its receptor. This is an interesting problem in many respects, but most intriguing are the observed differences in delivery efficiency in vivo compared with protein-free in vitro conditions. In order to understand possible situations that the nanoparticle will face in a protein-rich biological environment, we will first describe the formation of a protein corona and thereafter discuss potential perturbations of the delivery systems when moving from in vitro testing to in vivo applications. We emphasize the role of mathematical modeling in optimizing the design of functionalized nanoparticles to achieve high success of delivery.